Salivary Alpha Amylase Bronchial Measure for Early Aspiration Pneumonia Diagnosis in Patients Treated With Therapeutic Hypothermia After Out-of-hospital Cardiac Arrest - Moussali, Anis; Cauchois, Emi; Carvelli, Julien; Hraeich, Sami; Bouzana, Fouad; Lesaux, Audrey; Boucekine, Mohamed; Bichon, Amandine; Gainnier, Marc; Fromonot, Julien; Bourenne, Jeremy (Frontiers in Medicine, 2022)
Background Aspiration pneumonia is the most common respiratory complication following out-of-hospital cardiac arrests (OHCA). Alpha-amylase (α-amylase) in pulmonary secretions is a biomarker of interest in detecting inhalation. The main goal of this study is to evaluate the performance of bronchoalveolar levels of α-amylase in early diagnosis of aspiration pneumonia, in patients admitted to intensive care unit (ICU) after OHCA. Methods This is a prospective single-center trial, led during 5 years (July 2015 to September 2020). We included patients admitted to ICU after OHCA. A protected specimen bronchial brushing and a mini-bronchoalveolar lavage (mini-BAL) were collected during the first 6 h after admission. Dosage of bronchial α-amylase and standard bacterial analysis were performed. Investigators confirmed pneumonia diagnosis using clinical, radiological, and microbiological criteria. Every patient underwent targeted temperature management. Results 88 patients were included. The 34% (30 patients) developed aspiration pneumonia within 5 days following admission. The 55% (17) of pneumonias occurred during the first 48 h. The 57% of the patients received a prophylactic antibiotic treatment on their admission day. ICU mortality was 50%. Median value of bronchial α-amylase did not differ whether patients had aspiration pneumonia (15 [0–94]) or not (3 [0–61], p = 0,157). Values were significantly different concerning early-onset pneumonia (within 48 h) [19 (7–297) vs. 3 (0–82), p = 0,047]. If one or more microorganisms were detected in the initial mini-BAL, median value of α-amylase was significantly higher [25 (2–230)] than in sterile cultures (2 [0–43], p = 0,007). With an 8.5 IU/L cut-point, sensitivity and specificity of α-amylase value for predicting aspiration pneumonia during the first 2 days were respectively 74 and 62%. True positive and negative rates were respectively 44 and 86%. The area under the ROC curve was 0,654 (CI 95%; 0,524–0,785). Mechanical ventilation duration, length of ICU stay, and mortality were similar in both groups. Conclusion In our study, dosage of bronchial α-amylase was not useful in predicting aspiration pneumonia within the first 5 days after ICU admission for OHCA. Performance in predicting early-onset pneumonia was moderate.